La arteria cultural del cuerpo estatal: el campo de las Bellas Artes en la construcción del Estado liberal español (1833-1874) - Gilarranz Ibáñez, Ainhoa (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
In the 1990s, a group of historians reopened the debate on the building of nation states. Perspectives swung between a strong or a weak structure for European states. This cultural wave in contemporary history introduced new viewpoints that can now be summarised in a “bottom up” analysis of state building. Continuing with this line of thought, this work explores the possibilities opened up by adopting a cultural perspective of such a complex historical process. Specifically, how observing the artistic field, with its lines dividing institutions, symbolic universes and agents, could shed new light on nineteenth-century nation-state building.
Keywords: liberal State; 19th century; Cultural history; art